STRATEGI PENGEMBANGAN EKOWISATA KERUJUK DI KABUPATEN LOMBOK UTARA - Siwantari, Putu Ayu Pratiwi Duta; Purwata, I Ketut (Kepariwisataan: Jurnal Ilmiah, 2026)
ABSTRACTOne way to optimally utilize a region's potential is through ecotourism development. Developing a sustainable ecotourism destination requires a strategy. Kerujuk Ecotourism is a conservation-themed natural tourism destination, first discovered in North Lombok Regency. Several problems have been identified in its development, including a lack of proper ecotourism management, inadequate facilities and infrastructure, and low-quality community resources in the tourism sector. Consequently, the area's ecotourism potential is not realized in terms of economic activities and the welfare of the local population. The purpose of this study was to identify the potentials of Kerujuk Hamlet, identify factors influencing ecotourism development, and develop strategies for developing Kerujuk ecotourism. Data were collected through interviews, observations, questionnaires, and documentation. This study used a qualitative approach, analyzed using the IFAS and EFAS matrices, resulting in general strategies and alternative strategies that can be used to develop Kerujuk ecotourism. The results of the study indicate that the Kerujuk ecotourism development strategy is in quadrant V. Alternative strategies generated through SWOT analysis in the context of Kerujuk ecotourism development are as follows: collaborating with educational institutions, developing creative economic products by utilizing current trends, strengthening promotion and branding, reorganizing tourist areas, diversifying tourist attractions as risk mitigation, strengthening destination image, preparing clear SOPs and policies, and preparing cleaning and infrastructure improvement programs. Suggestions for the management can collaborate with the government in preparing facilities and infrastructure with established standard references without damaging the natural environment and forming institutions in good management to improve work professionalism.Keywords: Development Strategy; Conservation; Kerujuk Ecotourism; Sustainable Tourism; SWOT ABSTRAKSalah satu cara untuk memanfaatkan potensi suatu daerah secara optimal adalah melalui pengembangan ekowisata. Untuk mengembangkan destinasi ekowisata yang berkelanjutan, diperlukan strategi. Ekowisata Kerujuk adalah objek wisata alam bertema konservasi, yang pertama kali ditemukan di Kabupaten Lombok Utara. Beberapa masalah telah diidentifikasi dalam pengembangannya, termasuk kurangnya pengelolaan ekowisata yang tepat, fasilitas dan infrastruktur yang tidak memadai, dan kualitas sumber daya masyarakat yang rendah di sektor pariwisata, sehingga potensi ekowisata daerah tersebut tidak terealisasi dalam kegiatan ekonomi dan kesejahteraan penduduk setempat. Tujuan dilakukan penelitian ini yaitu untuk mengidentifikasi potensi-potensi yang terdapat pada Dusun Kerujuk, mengidentifikasi faktor-faktor yang mempengaruhi pengembangan ekowisata, serta strategi untuk mengembangkan ekowisata Kerujuk. Data dikumpulkan melalui wawancara, observasi, kuesioner, dan dokumentasi. Studi ini menggunakan pendekatan kualitatif, dianalisis menggunakan matriks IFAS dan EFAS, menghasilkan strategi umum dan strategi alternatif yang dapat digunakan untuk mengembangkan ekowisata Kerujuk. Hasil penelitian menunjukkan bahwa strategi pengembangan ekowisata Kerujuk berada di kuadran V. Strategi alternatif yang dihasilkan melalui analisis SWOT dalam konteks pengembangan ekowisata Kerujuk adalah sebagai berikut: berkolaborasi dengan lembaga pendidikan, mengembangkan produk ekonomi kreatif dengan memanfaatkan tren terkini, memperkuat promosi dan branding, menata ulang kawasan wisata, mendiversifikasi objek wisata sebagai mitigasi risiko, memperkuat citra destinasi, menyiapkan SOP dan kebijakan yang jelas, serta menyiapkan program pembersihan dan peningkatan infrastruktur. Saran bagi pihak pengelola dapat bererjasama dengan pemerintah dalam menyiapkan sarana dan prasarana dengan acuan standar yang telah ditetapkan tanpa merusak lingkungan yang masih alami serta membentuk kelembagaan dalam pengelolaan dengan baik agar meningkatkan profesionalisme kerja.Kata kunci: Strategi Pengembangan; Konservasi; Ekowisata Kerujuk; Pariwisata Berkelanjutan; SWOT